Modeling and Evaluation of Mutual Coupling Effect in Conventional Switched Reluctance Machines Using Space Vector Representation - Peter Azer; Sumedh Dhale; Milan Kordic; Ali Emadi (IEEE Access)
This paper presents a non-linear model for conventional switched reluctance machines (CSRMs) that considers the mutual coupling between phases. Although CSRMs are based on single-phase excitation, there is usually an overlapping between the excited phases. During this overlapping, the CSRM is at 2-phase excitation and the single-phase representation of motor dynamics is not accurate. Hence, a dynamic model is presented in this paper that that accounts for the the mutual coupling between phases in addition to the effects of saturation and spatial harmonics. The proposed method is based on modeling the resultant current vector due to 2-phase excitation in space. The relationship between the resultant current and flux linkage vectors is obtained at different rotor positions using finite element method (FEM). This relationship is saved as a 3D lookup table (LUT). These 3D LUTs are reduced into 2D LUTs independent of rotor position by representing the phase currents as vectors instead of instantaneous values. Similarly, the relationship between the resultant current vector and the electromagnetic torque is obtained and saved as a 3D lookup table. The proposed method is compared with a conventional model where the mutual coupling is not considered. This comparison is conducted using FEM on two different motors; the first motor is 12/8 3-phase 2kW CSRM and the second motor is 24/16 3-phase 75kW CSRM. FEM results show that the mutual coupling is significant for high power motors. The proposed dynamic model is compared with experimental results using the 12/8 3-phase 2kW CSRM.